Set identification via quantile restrictions in short panels - Adam Rosen (Centre for Microdata Methods and Practice (cemmap), 2009)
This paper studies the identifying power of conditional quantile restrictions in short panels with fixed effects. In contrast to classical fixed effects models with conditional mean restrictions, conditional quantile restrictions are not preserved by taking differences in the regression equation over time. This paper shows however that a conditional quantile restriction, in conjunction with a weak conditional independence restriction, provides bounds on quantiles of differences in time-varying unobservables across periods. These bounds carry observable implications for model parameters which generally result in set identification. The analysis of these bounds includes conditions for point identification of the parameter vector, as well as weaker conditions that result in identification of individual parameter components.
Keywords: 330; bound analysis; conditional quantiles; partial identification; panel data; fixed effects; Mathematik